Mortality among adults: gender and socioeconomic differences in a Brazilian city - Belon, Ana Paula (BioMed Central, 2012)
BACKGROUND: Population groups living in deprived areas are more exposed to several risk factors for diseases and injuries and die prematurely when compared with their better-off counterparts. The strength and patterning of the relationships between socioeconomic status and mortality differ depending on age, gender, and diseases or injuries. The objective of this study was to identify the magnitude of social differences in mortality among adult residents in a city of one million people in Southeastern Brazil in 2004-2008. METHODS: Forty-nine health care unit areas were classified into three homogeneous strata using 2000 Census small-area socioeconomic indicators. Mortality rates by age group, sex, and cause of death were calculated for each socioeconomic stratum. Mortality rate ratios (RR) and 95% confidence intervals were estimated for the low and middle socioeconomic strata compared with the high stratum. RESULTS: In general, age-specific mortality rates showed a social gradient of increasing risks of death with decreasing socioeconomic status. The highest mortality rate ratios between low and high strata were observed in the 30-39 age group for males (RR = 1.74, 95% CI 1.59-1.89), and females (RR = 1.90, 95% CI 1.65-2.15). Concerning specific diseases and injuries, the greatest inequalities between low and high strata were found for homicides (RR = 2.44, 95% CI 2.27-2.61) and traffic accidents (RR = 1.64, 95% CI 1.45-1.83) among males. For women, the highest inequalities between the low and high strata were for chronic respiratory diseases (RR = 2.19, 95% CI 1.94-2.45) and acute myocardial infarction (RR = 1.93, 95% CI 1.79-2.07). Only breast cancer showed a reversed social gradient (RR = 0.70, 95% CI 0.48-0.92). Inequalities in circulatory and respiratory diseases mortality were greater among females than among males. CONCLUSIONS: Substandard living conditions are related to unhealthy behaviors, as well as difficulties in accessing health care. Therefore, the Brazilian Health System (SUS) must ensure greater access to primary and hospital care, and develop programs that promote healthier lifestyles among vulnerable groups to reduce social inequalities in mortality. Moreover, because deaths from external causes are concentrated in poor areas, cooperative and coordinated intersectoral actions should be taken to combat the deadly violence cycle.